The nexus between child streetism and delinquency in Nigeria: Implications for sustainable development - Taiwo, Amos Oluwole (Universitas Trunojoyo Madura, 2024)
Child streetism and delinquency present significant social challenges in Nigeria, where children engaged in street life are often exposed to criminal activities and adverse socio-economic conditions. This study explores the relationship between child streetism and delinquency, and their implications for sustainable development. Utilizing a systematic review methodology, the study critically analyses 61 key sources published between 1969 and 2023, including peer-reviewed journal articles, reports from international organizations, and empirical studies, to explore the definitions, contexts, and empirical evidence related to street children and their behaviors, risks, and socio-environmental impacts in Nigeria. It reveals a significant relationship between child streetism and delinquency, highlighting that children engaged in street work often participate in various negative behaviors such as drug trafficking, thuggery, sexual assault, and cultism. These issues severely impact their psychological and moral development, contributing to broader societal challenges and undermining sustainable development efforts. The paper identifies persistent socio-economic and cultural factors within the family and society as key drivers of child streetism and delinquency behavior in Nigeria, with current government initiatives failing to address these root causes effectively. The study concludes by suggesting a collaborative, multistakeholder approach to effectively address the complex issues surrounding street children and delinquency in Nigeria.